Los avatares de la realidad histórica: Sobre la filosofía de Ignacio Ellacuría - Romero Cuevas, José Manuel (2022)
The present article approaches the process of the constitution of meaning of the concept of historical reality, central to the philosophy of Ignacio Ellacuría. Through Ellacuría’s texts and step by step, the articlefollows his reception and interpretation of the work of X. Zubiri, in dialogue with whom he shapeshis Philosophy of Historical Reality. The aim is to contribute to the understanding of the scope andoriginality of Ellacuría’s philosophy.